Natural Gas as a Key Alternative Energy Source in Sustainable Renewable Energy Transition: A Mini Review - Mohammad, Norsyahida; Mohamad Ishak, Waznatol Widad; Mustapa, Siti Indati; Ayodele, Bamidele Victor (Frontiers in Energy Research, 2021)
Energy security and sustainability are undeniably the main concerns in combatting climate change. While an immediate call for all-green and renewable energy seems to be impossible due to huge financial implications and inadequate supporting energy structure, an alternative to fossil fuels needs to be established. Natural gas, a naturally occurring fossil gas is a cleaner energy source option compared to other fossil fuels such as coal, bitumen, and diesel. Natural gas makes the best fit for a sustainable renewable energy transition in any country around the globe due to its competitiveness towards other fossil fuels such as coal and its ability to aid the integration of renewables. This review highlights the technological pathways of utilizing natural gas in a transition to sustainable renewable energy systems, with a focus on the natural gas components and resources point of view for ASEAN member states (AMS). Policies that support the development of natural gas as a key alternative energy source in sustainable renewable energy transition would also be reviewed. This review aims to provide a thorough guide to researchers, stakeholders, and policymakers to construct and support efficient, reliable, affordable, sustainable, and environmentally friendly energy systems utilizing the abundant inexpensive natural gas.